2017
DOI: 10.1007/s10548-017-0563-1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Dream Recall: EEG Activation During NREM Sleep or Shared Mechanisms with Wakefulness?

Abstract: The common knowledge of a uniqueness of REM sleep as a privileged scenario of dreaming still persists, although consolidated empirical evidence shows that the assumption that dreaming is just an epiphenomenon of REM sleep is no longer tenable. However, the brain mechanisms underlying dream generation and its encoding in memory during NREM sleep are still mostly unknown. In fact, only few studies have investigated on the mechanisms of dream phenomenology related to NREM sleep. For this reason, our study is spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 55 publications
(108 reference statements)
7
61
0
Order By: Relevance
“…During N2, dreaming was associated with reduced <1 Hz activity and concomitantly increased power above 4 Hz. Although differing in the specific frequency bands identified, this observation is broadly consistent with prior reports that dreaming is predicted by reduced low-frequency power in the delta range (Esposito et al, 2004;Scarpelli et al, 2017;Siclari et al, 2017). As low-frequency power is inversely related to regional cerebral blood flow during sleep (Dang-Vu et al, 2005;Hofle et al, 1997), our observations support the long-standing hypothesis that dreaming outside of REM sleep occurs during periods of relatively heightened cortical "activation" (Antrobus, 1991;Scarpelli et al, 2017;Wamsley et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…During N2, dreaming was associated with reduced <1 Hz activity and concomitantly increased power above 4 Hz. Although differing in the specific frequency bands identified, this observation is broadly consistent with prior reports that dreaming is predicted by reduced low-frequency power in the delta range (Esposito et al, 2004;Scarpelli et al, 2017;Siclari et al, 2017). As low-frequency power is inversely related to regional cerebral blood flow during sleep (Dang-Vu et al, 2005;Hofle et al, 1997), our observations support the long-standing hypothesis that dreaming outside of REM sleep occurs during periods of relatively heightened cortical "activation" (Antrobus, 1991;Scarpelli et al, 2017;Wamsley et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…This feature of working memory may similarly be critical for remembering a dream. Support for this claim is that increased cortical activation is a prerequisite for dream recall; in particular, theta (5-8 Hz) electroencephalograph (EEG) oscillations on frontal regions (Scarpelli et al, 2015), along with decreased delta over frontal and temporo-parietal areas (Scarpelli et al, 2017) in pre-awakening sleep, are predictive of dream recall. These findings parallel the relationship between theta activity and working memory during wake (Sauseng et al, 2010), and although these observations have been interpreted as state-dependent factors in dream recall, our present verbal fluency findings support a trait-like influence of working memory capacity on dream recall.…”
Section: Discussionmentioning
confidence: 99%
“…Many features of brain electrophysiology have been investigated and reported to correlate with different conscious processes or even the level of consciousness. Spectral power differences have been commonly found at characteristic frequency bands; notably, lack of consciousness has been associated with increased power at low frequencies (delta waves: <4 Hz) in multiple contexts, including sleep stage depth, dream recall within a sleep stage, and anaesthetic depth (Chellappa et al, 2011;Evans, 2003;Hobson & Pace-Schott, 2002;Murphy et al, 2011;Scarpelli et al, 2017;Siclari et al, 2017Siclari et al, , 2018Thomsen, Rosenfalck, & Nørregaard Christensen, 1991). Higher levels of consciousness (or arousal) have also been suggested to correlate with a lower spectral exponent (Colombo et al, 2019), higher signal entropy or complexity (Bein, 2006;Bruhn, Röpcke, & Hoeft, 2000;D'Andola et al, 2017;Hudetz, Liu, Pillay, Boly, & Tononi, 2016;King et al, 2013;Liang et al, 2013;Ouyang, Li, Liu, & Li, 2013;Sarasso et al, 2015;Schartner et al, 2015), stronger phase coherence between brain areas (Bola et al, 2017;Lee et al, 2017;Mikulan et al, 2017), and more causally integrated brain areas (Barrett et al, 2012;D'Andola et al, 2017;Fasoula, Attal, & Schwartz, 2013).…”
Section: Measures Of Consciousnessmentioning
confidence: 99%
“…No clustering was required. To make their final blind classification, the Analysis Team replicated three measures based on the significant differences reported by Siclari et al (2017) and Scarpelli et al (2017), both of which had been recently published. Two of the features were Siclari et al's low and high frequency hot zone power, named respectively SBP low and SBP high (SBP for the initials of the first three authors of the Siclari paper), and one feature was the low frequency activity reported by Scarpelli et al, named Scarpelli (see Supplementary Document 6 for full details).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation